Strategic implementation of verbs of communication in English business discourse - Galina A. Parshutina; Ksenia V. Popova (Peoples' Friendship University of Russia (RUDN University), 2018)
The study explores verbs of communication in terms of their functional and practical implementation in business negotiations, interviews and political debates. The study relies on corpus data and appeals to componential, comparative, contextual, semantic, pragmatic and functional methods of analysis to consider verbs of communication as a developing functional system. The authors suggest that verbs of communication act as strategic drivers of English business discourse and are involved in not only nominating speech acts, but also in generating contextually relevant interaction whereby a statement is placed in a wider context of external communicative settings. The study concludes that verbs of communication can help control and model verbal interaction, provide coherence of propositional structure, comprehend the distribution of roles, and create pragmatic dynamics of narration, which is why they present an integral part of the business discourse system and function as integrating components of a set of communicative tactics foregrounding diverse communicative strategies.